PARTISIPASI KARYAWAN UNTUK KEBERLANJUTAN PRODUKSI CAT EMPLOYEE PARTICIPATION FOR SUSTAINABILITY OF PAINT PRODUCTION - Sri Wrinarti; Tri Edhi Budhi Soesilo; Sri Listyarini (Jurnal Matematika Sains dan Teknologi, 2015)
Paint production generates hazardous and toxic waste. The amount of waste can be reduced if the paint factory employees, especially in the Production and Health Safety Environment & Security units, participates to reduce the amount of waste in accordance with the company's target for the sustainability of the paint production. Currently, PT. XYZ, a paint industry, has never conducted a survey to determine the role of its employees to reduce the amount of waste. This study was conducted to analyze the employee perception of their role to reduce the amount of waste. To analyze the perception of the role of employees, a survey of 93 respondents was conducted. The value of the role of respondents to reduce the amount of waste is 4.93 out of 6. In conclusion, the value of the role of respondent perception to reduce the amount of waste is 4.93 in six scales. Produksi cat menghasilkan limbah Bahan Berbahaya dan Beracun. Jumlah limbah pabrik cat dapat dikurangi apabila karyawan pabrik, khususnya di bagian Produksi dan Health Safety Environment & Security, berpartisipasi untuk menurunkan jumlah limbah sesuai dengan target perusahaan untuk keberlanjutan produksi cat. Saat ini PT. XYZ, sebuah industri cat, belum pernah melakukan survei untuk mengetahui peranan karyawannya untuk menurunkan jumlah limbahnya. Penelitian dilakukan untuk menganalisis persepsi karyawan tentang peranan mereka untuk menurunkan jumlah limbah. Untuk menganalisis persepsi peranan karyawan, telah dilakukan survei terhadap 93 responden. Nilai persepsi karyawan tentang peranan mereka untuk menurunkan jumlah limbah adalah 4,93 dari skor maksimum 6. Kesimpulannya, nilai persepsi karyawan tentang peranan mereka untuk menurunkan jumlah limbah adalah 4,93 dari 6 skala.